(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
The effects of the herbicide nicosulfuron on the abundance of cellulolytic and proteolytic microorganisms, activity of â-glucosidase and protease enzymes, and microbial phosphorus biomass were examined. A laboratory bioassay was set up on two types of agricultural soils differing in physicochemical properties. The following concentrations were tested: 0.3, 0.6, 3.0 and 30.0 mg a.i./kg of soil. Samples were collected 3, 7, 14, 30 and 45 days after treatment with nicosulfuron. The results showed that nicosulfuron significantly reduced the abundance of cellulolytic microorganisms in both soils, as well as microbial biomass phosphorus in sandy loam soil. The herbicide was found to stimulate â-glucosidase and protease activity in both types of soil and microbial biomass phosphorus in loamy soil. Proteolytic microorganisms remained unaffected by nicosulfuron.